1999
DOI: 10.1021/jp990389g
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Alcohols with Hydroxyl- and Methyl-Terminated Self-Assembled Monolayer Surfaces Studied by Temperature-Programmed Desorption

Abstract: The interactions of low-molecular-weight n-alcohols (n-C x H 2x+1 OH for x ) 1-6) with 11-mercaptoundecanol (HO(CH 2 ) 11 SH) or octadecyl mercaptan (CH 3 (CH 2 ) 17 SH) adsorbed onto a nickel(111) single-crystal surface were studied by temperature-programmed desorption (TPD). Angle-dependent X-ray photoelectron spectroscopy (ADXPS) was used to characterize the adsorption of HO(CH 2 ) 11 SH and CH 3 (CH 2 ) 17 SH molecules to determine their arrangements on the nickel(111) surface. The TPD spectra for the deso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
(59 reference statements)
0
11
0
Order By: Relevance
“…Another plausible origin of the second-order kinetics of adsorbates is their surface diffusion, which can produce a long tail in the high-temperature side of the TPD peaks . For example, Vogt et al reported that the TPD spectra for alcohol molecules adsorbed on SAMs display a second-order desorption (or symmetric) profile due to their diffusion on the SAM surfaces . It is conceivable that the surface diffusion of the clusters leads to a random orientation in the desorption process and that the IRAS spectra for the V(benzene) 2 /gold represent the random orientation of the clusters at any surface temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Another plausible origin of the second-order kinetics of adsorbates is their surface diffusion, which can produce a long tail in the high-temperature side of the TPD peaks . For example, Vogt et al reported that the TPD spectra for alcohol molecules adsorbed on SAMs display a second-order desorption (or symmetric) profile due to their diffusion on the SAM surfaces . It is conceivable that the surface diffusion of the clusters leads to a random orientation in the desorption process and that the IRAS spectra for the V(benzene) 2 /gold represent the random orientation of the clusters at any surface temperature.…”
Section: Discussionmentioning
confidence: 99%
“…The recent work by Vogt and co-workers shows similar preexponential factors for the desorption of small alcohol molecules from the surface of an OH-terminated self-assembled monolayer. 56 Their temperature-programmed desorption studies indicated that surface diffusion into and subsequently out of the monolayer plays a significant role in the overall dynamics. Diffusion of surfacebound HCl molecules into the SAM may also contribute to the overall scattering dynamics in the work presented here.…”
Section: Activation Energymentioning
confidence: 99%
“…When the resulting clusters are weakly physisorbed on the substrate, their structures are relatively unperturbed and retain many of the properties of their gas-phase counterparts. This is a key requirement for the organometallic sandwich clusters, because their unique properties originate from their 1D sandwich structures. However, such a weak surface interaction usually permits thermal desorption of the clusters well below room temperature because of a relatively small desorption activation energy (or adsorption heat) of physisorption. Hence, it is highly desirable to achieve a much larger adsorption heat of the soft-landed clusters while keeping them intact on the substrate.…”
mentioning
confidence: 99%
“…The second-order desorption kinetics observed on the clean gold surface is likely due to the surface diffusion of the adsorbed clusters prior to desorption, because the diffusion activation energy on metal substrates is usually small enough to permit quasi-free two-dimensional diffusion of molecular adsorbates , On the other hand, the first-order desorption kinetics of VBz 2 on the long-chain SAM substrates indicates that the clusters are desorbed directly from the SAM without significant intercluster interactions. Moreover, the unusually large desorption activation energy (i.e., >1 eV) manifests the presence of a significant physical effect in the VBz 2 adsorption for the SAM substrate.…”
mentioning
confidence: 99%